An expression is shown

-3a(a + b - 5) + 4(-2a + 2b) + b(a + 3b - 7)

Which expression is equivalent to the expression shown?

A.) -11a² + 3b² - 2ab + 7a + b

B.) -11a² + 3b² - 4ab + 7a = b

C.) -3a² + 3b² - 2ab + 7a + b

D.) -3a² + 3b² - 4ab + 7a + b

-3a(a + b - 5) + 4(-2a + 2b) + b(a + 3b - 7)

Which expression is equivalent to the expression shown?

A.) -11a² + 3b² - 2ab + 7a + b

B.) -11a² + 3b² - 4ab + 7a = b

C.) -3a² + 3b² - 2ab + 7a + b

D.) -3a² + 3b² - 4ab + 7a + b

-3a(a + b - 5) + 4(-2a + 2b) + b(a + 3b - 7)

= -3a² - 3ab + 15a - 8a + 8b + ab + 3b² - 7b {used distributive property}

=

= -3a² - 3ab + 15a - 8a + 8b + ab + 3b² - 7b {used distributive property}

=

**-3a² + 3b² - 2ab + 7a + b**{combined like terms}*- Algebra House*